Determinants of Governmental Redistribution: Income Distribution, Development Levels, and the Role of Perceptions - Sebastian Köllner; Klaus Gründler (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
We empirically investigate the relationship between income inequality and redistribution, accounting for the shape of the income distribution, different development levels, and subjective perceptions. Cross-national inequality datasets that have become available only recently allow for the assessment of the link for various sample compositions and several model specifications. Our results confirm the Meltzer-Richard hypothesis, but suggest that the relation between market inequality and redistribution is even stronger when using perceived inequality measures. The findings emphasize a decisive role of the middle class, though also approving a negative impact of top incomes. The Meltzer-Richard effect is less pronounced in developing economies with less sophisticated political rights, illustrating that it is the political channel through which higher inequality translates into more redistribution.
Keywords: C23; D31; H11; 330